Identifikasi pemahaman dan implementasi pendidikan lingkungan hidup di SMP YPK 2 Fanindi Kabupaten Manokwari Papua Barat - Rumayomi, Merpati C; Warami, Hugo; Martanto, Eko Agus (Cassowary, 2025)
ABSTRACT: Schools as educational institutions are the main target in environmental management efforts through implementation in subjects. Environmental education is a character education. Understanding of the environment has been included in one subject based on an agreement between the Minister of Environment and the Minister of National Education. SMP YPK 2 Fanindi Manokwari is expected to implement environmental education. It is necessary to know the understanding of the implementation of environmental education and also the implementation of environmental education at SMP YPK 2 Fanindi Manokwari and the results can provide an overview of the understanding and implementation of environmental education at SMP YPK 2 Fanindi Manokwari. This research uses descriptive methods and interview, observation and archiving techniques. The results of this study indicate that the application of environmental education has not been applied but in practice it has been applied in everyday life at SMP YPK 2 Fanindi Manokwari.